Across space and time
1 online resource (xxv, 304 pages)
Keywords: "Modernity tends to be considered a mostly Western, chronologically recent concept. Looking at locations in Brazil, Java, India, Georgia, and Yugoslavia, among others, Across Space and Time provides architectural and cultural evidence that modernity has had an impact across the globe and for much longer than previously conceived. This volume moves through space and time to illustrate the way global modernity has been negotiated through architecture, urban planning, design pedagogies, preservation, and art history in diverse locations around the world. Bringing together emerging and established architecture and art history scholars, each chapter focuses on a particular site where modernity was defined, challenged, or reinterpreted. The contributors examine how architectures, landscapes, and design thinking influence and are influenced by conflicts between cultural, economic, technological, and political forces. By invoking well-researched histories to ground their work in a post-colonial critique, they closely examine many prevailing myths of modernity. Notable topics include emerging architectural history in the Indian subcontinent and the connection between climate change and architecture. Ultimately, Across Space and Time contributes to the ongoing critique of architecture and its history, both as a discipline and within the academy. The authors insist that architecture is more than a style. It is a powerful expression of representational power that reveals how a society negotiates its progress."--Provided by publisher.